1987
DOI: 10.1002/bip.360261002
|View full text |Cite
|
Sign up to set email alerts
|

A Brillouin scattering study of the hydration of Li‐ and Na‐DNA films

Abstract: SynopsisWe have used Brillouin spectroscopy to study the velocities and attenuation of acoustic phonons in wet-spun films of Na-DNA and Li-DNA as a function of the degree of hydration at room temperature. Our data for the longitudinal acoustic (LA) phonon velocity vs water content display several interesting features and reveal effects that we can model at the atomic level as interhelical bond softening and relaxation of the hydration shell. The model for interhelical softening makes use of other physical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 31 publications
2
68
0
Order By: Relevance
“…Phase matching for SBS is thus defined by both 1 arXiv:1408.1739v2 [physics.optics] 11 Aug 2014 energy and momentum conservation, and is satisfied in back-scattering only by multi-GHz phonon modes in most solids. SBS is frequently used for optical gain [3,13], laser linewidth narrowing [14], optical phase conjugation [15], dynamic gratings [16], and even material characterization and microscopy [17][18][19][20][21][22]. The applications of SBS in superluminal and slow light experiments have been recognized as well [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Phase matching for SBS is thus defined by both 1 arXiv:1408.1739v2 [physics.optics] 11 Aug 2014 energy and momentum conservation, and is satisfied in back-scattering only by multi-GHz phonon modes in most solids. SBS is frequently used for optical gain [3,13], laser linewidth narrowing [14], optical phase conjugation [15], dynamic gratings [16], and even material characterization and microscopy [17][18][19][20][21][22]. The applications of SBS in superluminal and slow light experiments have been recognized as well [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The variation of the hydration of the oriented DNA fibers means that the water content and thus the DNA-DNA helix axis separation is varied. 15 In addition, we have studied the salt dependence of the 7Li+ quadrupolar splitting of a sample in equilibrium with a C2H60D-D20-LiC1 solution. This setup has enabled us to vary the salt content in an individual sample.…”
Section: Introductionmentioning
confidence: 99%
“…These values are considerably higher than the modulus of about 300 MPa that was determined in single-molecule stretching experiments in solution (6,22). However, Brillouin scattering studies have previously found that at low levels of hydration, the modulus of DNA films strongly increases to values of 9.3-11.6 GPa at a relative humidity of 23% (21,23). Our results are therefore consistent with a low level of DNA hydration, and this justifies our choice of the value for the density of DNA.…”
Section: Resultsmentioning
confidence: 67%